Pengaruh Peran Influencer Dan Literasi Halal Terhadap Keputusan Pembelian Produk Skincare Dimediasi Oleh Kesadaran Halal (Studi Kasus Mahasiswa PTMA di Yogyakarta) - Isyah Alvionita; Dyah Pikanthi Diwanti (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the influence of influencers and halal literacy on skincare product purchasing decisions with halal awareness as a mediating variable among PTMA students in Yogyakarta. This study used a quantitative approach with a survey method through distributing questionnaires to respondents, and analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique. The results showed that the role of influencers had a positive and significant effect on purchasing decisions, but did not significantly influence halal awareness. Conversely, halal literacy had a positive and significant effect on halal awareness, but did not have a significant direct effect on purchasing decisions. Halal awareness was proven to have a positive and significant effect on purchasing decisions. In addition, halal awareness was able to mediate the influence of halal literacy on purchasing decisions, but was unable to mediate the influence of the role of influencers on purchasing decisions.